2020
DOI: 10.1182/bloodadvances.2019001032
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular profiling of T-cell subsets at the onset of human acute GVHD

Abstract: The cellular and molecular processes involved in acute graft-versus-host disease (aGVHD) development early after allogeneic hematopoietic cell transplantation (HCT) in humans remain largely unknown. We have performed multiparameter immunophenotyping and molecular profiling of CD4+ and CD8+ T cells in 2 independent cohorts of patients undergoing HCT, as well as in their HLA-identical sibling donors. Cellular profiling using spectral flow cytometry showed an incomplete reconstitution of the T-cell compartment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Additionally, the thymus of NSG mice atrophies shortly after birth and is completely absent by 4-6 weeks of age, negating the likelihood of de novo T cell production in these model systems. The same effector memory phenotype has also been identified in several primary human T cells clones taken from GVHD patients (49)(50)(51)(52). While there has not been a study directly investigating the capacity of isolated human memory T cells to mediate GVHD in a xenogeneic transplant model, studies using human umbilical cord blood T cells (which are all naïve CD45RA + T cells) also detect a universal transition to an effector memory phenotype several weeks after transplantation (47).…”
Section: Human T Cell Reactivity After Xenogeneic Transplantationmentioning
confidence: 82%
“…Additionally, the thymus of NSG mice atrophies shortly after birth and is completely absent by 4-6 weeks of age, negating the likelihood of de novo T cell production in these model systems. The same effector memory phenotype has also been identified in several primary human T cells clones taken from GVHD patients (49)(50)(51)(52). While there has not been a study directly investigating the capacity of isolated human memory T cells to mediate GVHD in a xenogeneic transplant model, studies using human umbilical cord blood T cells (which are all naïve CD45RA + T cells) also detect a universal transition to an effector memory phenotype several weeks after transplantation (47).…”
Section: Human T Cell Reactivity After Xenogeneic Transplantationmentioning
confidence: 82%
“… 17 Multianalyte profiling of culture supernatants was performed with Luminex xMAP technology (Myriad-RBM, Austin, Texas, USA), gene expression analysis with nCounter Technology (NanoString), with the Human Immunology v2 Gene Expression CodeSet. 18 19 …”
Section: Methodsmentioning
confidence: 99%
“…In the data presented here, the T SCM CD122 hi subset had significantly upregulated Il12rb2 and Il18rap, along with the LN homing receptor and chemokine Ccr6 and Cxcr6, suggesting an activated memory-cell like transcriptomic profile that allows better ability to sense and respond to recall antigen challenge. By contrast, the T SCM CXCR3 hi subset had high expression of cytotoxicity-associated genes, such as Znf683 (also known as Hobit) and Il12rb1, and downregulated the memory-associated genes Klrf1 and Klrb1, as well as genes involved in T-cell stimulation and activation (Tryobp, Vav3, Gch1, and Efhd2), suggesting effector-cell like properties [64][65][66]. This finding is consistent with a recent report [52], which suggested that CXCR3-expressing T N cells are poised for effector potential.…”
Section: Discussionmentioning
confidence: 99%